Réponses

Meilleure réponse !
2014-03-29T13:47:12+01:00
Bonjour

a{ 4x-3y=6
 { x+5y=13
on élimine les x en multipliant la 2ème équation par -4
4x -3y = 6
-4x - 20y = - 52

-23y = - 46
y = 2
x + 10 = 13
x = 13 -10
x = 3

Vérification : 12 - 6 = 6 ⇒ 6 = 6

b { -5x+1.5y=18
 {-x+2.5y=8

-5x +1.5 y = 18
+5x - 12.5y = - 40

- 11y= - 22 ⇒ y = 2
-x + 5 = 8
-x = 8 -5
-x = 3 ⇒ x = -3
Vérification :  3 + 5 = 8

c{2x+3y=5
 {4x+15y=37

- 4x - 6y = -10
4x + 15y = 37
9y = 27
y = 3
2x + 9 = 5
2x = 5 -9
2x = -4
x = -2
Vérification : -4 + 9 = 5 ⇒ 5 = 5

d{ 2x+3y=5
 {3x+2y=-1


on élimine les y en * la 1ere équation par  -2 et la seconde par 3

on a :
-4x -6y = -10
6x + 6y = -3

2x = -13 et x = -6.5
-13 +3 y = 5
3y = 5 +13
3y = 18
y = 6
vérification
2x +3y = 5
-13 + 18 = 5
5 = 5